2012
DOI: 10.1042/an20120035
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblast Migration and P2Y1Receptor Mediated Calcium Signalling Depend on 9-O-Acetyl GD3 Ganglioside

Abstract: Previous studies indicated that a ganglioside 9acGD3 (9-O-acetyl GD3) antibody [the J-Ab (Jones antibody)] reduces GCP (granule cell progenitor) migration in vitro and in vivo. We here investigated, using cerebellar explants of post-natal day (P) 6 mice, the mechanism by which 9acGD3 reduces GCP migration. We found that immunoblockade of the ganglioside with the J-Ab or the lack of GD3 synthase reduced GCP in vitro migration and the frequency of Ca2+ oscillations. Immunocytochemistry and pharmacological assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 62 publications
(96 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, postnatal granule cell precursors of the cerebellum migrate and then differentiate into excitatory granule cells and integrate into the cerebellar circuitry (Ito, ). The antagonism of P2Y1Rs and the immunoblockade of gangliosides similarly reduced the frequency of Ca 2+ oscillations of granule cell precursors and their migration into the cerebellum (Santiago and Scemes, ).…”
Section: Proliferation Migration Differentiation and Necrosis/apopmentioning
confidence: 99%
“…Furthermore, postnatal granule cell precursors of the cerebellum migrate and then differentiate into excitatory granule cells and integrate into the cerebellar circuitry (Ito, ). The antagonism of P2Y1Rs and the immunoblockade of gangliosides similarly reduced the frequency of Ca 2+ oscillations of granule cell precursors and their migration into the cerebellum (Santiago and Scemes, ).…”
Section: Proliferation Migration Differentiation and Necrosis/apopmentioning
confidence: 99%
“…influences the cellular distribution and function of the purinergic receptor P2Y(1)R, controlling the migration of cerebellar granule-cell progenitors (Santiago & Scemes, 2012). Future studies are necessary to determine whether similar developmental changes would also occur in the visual system of GD3s -/mice, being associated with the phenotype described here.…”
Section: Discussionmentioning
confidence: 76%
“…The complete absence of staining in the SVZ of perfused (in which blood cells are absent in the brain) GD3 synthase-null mice, that exclusively lack all b- and c-series gangliosides [ 55 ], supports that hypothesis (data not shown). Moreover, we have recently shown that cerebellar progenitors cells extract from the same ganglioside null mice do not react at all with anti-9acGD3 antibodies [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunoblockage of CD60b also inhibits the radial migration of cerebellar granule cells in the developing rat cerebellum [ 16 , 19 ] and tangential neuroblast migration from postnatal SVZ explants [ 20 ]. Furthermore, CD60b-dependent calcium signaling through purinergic receptors was described as crucial for the migration of granular cell precursors during development [ 21 ]. In the adult peripheral nervous system, CD60b is re-expressed in the sciatic nerve after a crush injury, and its expression correlates with the axonal outgrowth through the lesion site [ 22 ].…”
Section: Introductionmentioning
confidence: 99%